Screening Epidemiological Characteristics of Blood Pressure in Schoolchildren from Ivano-Frankivsk - O.V. Urbas (Zaslavsky O.Yu., 2015)
The article presents the results of the epidemiological study carried out in the group of 1352 schoolchildren aged 12-17 years from Ivano-Frankivsk. Parameters of systolic and diastolic blood pressure and the ranges of fluctuations of its normal values were obtained in children of different age and sex groups. It is found that the incidence of high blood pressure episodes in schoolchildren aged 12-17 years from Ivano-Frankivsk (90-95 percentile) was 30.39 % in the boys and 14.68 % in the girls.